Building a novel strategic research agenda for METROFOOD-RI: design process and multi-stakeholder engagement towards thematic prioritization - Stelzl, Tamara; Tsimidou, Maria Z.; Belc, Nastasia; Zoani, Claudia; Rychlik, Michael (Frontiers in Nutrition, 2023)
Introduction The European research landscape suffers widely from fragmentation and little cross-border research collaboration. Efforts are underway to bring the European Research Area to a higher level of performance and capacity in cutting-edge science, with high anticipations for the promotion of multidisciplinary research infrastructures of transnational engagement. A European distributed research infrastructure active in this framework is METROFOOD-RI, committed to promoting metrology in food and nutrition with particular focus on measurement research related to agrifood systems. Methods For research infrastructures, streamlining resources among partner organizations and establishing priorities around specific topics is critical for ensuring smooth operation. Similarly, METROFOOD-RI faced the challenge of exploring its strategic direction and research priorities as revealed in its first Strategic Research and Innovation Agenda (SRIA). This report details how the internal process of topic identification and prioritization progressed within the METROFOOD-RI SRIA and what obstacles were encountered along the way. A dual-track strategy was taken for locating future SRIA topics, applying a top-down and bottom-up approach, followed by internal consultation with METROFOOD-RI experts. The topic prioritization drew on a vote among the METROFOOD-RI Management Committee employing a custom-designed numerical rating scale questionnaire. Based on the maximum scores obtained for each topic, appropriate thresholds were introduced for classifying individual topics into high, medium, low, and very low priority ones. Results A total of 80 topics categorized into eight major clusters of challenges were located as potential SRIA candidates. Upon prioritization, 9 topics of very high priority and 16 topics of medium priority were identified as key research thematic areas of the newly developed SRIA. Discussion As a strategic framework, the SRIA occupies a central position and sets not only the scientific focus of the research infrastructure in the coming years, but also contributes to realizing the full potential and excellence of METROFOOD-RI, selectively expanding the existing portfolio and thus contributing to maximum efficiency and sustainability. It is anticipated that the lessons learned by METROFOOD-RI and its experiences shared are a valuable stimulus and guide for those who are taking on the challenge of setting-up a SRIA and are looking for edifying and constructive information on how to do so.